Diagnostic performance of the fragmented QRS complex on electrocardiogram for detecting myocardial scars assessed by 3.0 Tesla cardiac magnetic resonance imaging - Kasin Viriyanukulvong, MD, MSc; Nonthikorn Theerasuwipakorn, MD, MSc; Wanwarang Wongcharoen, MD; Paisit Kosum, MD, MSc; Ronpichai Chokesuwattanaskul, MD, MSc (Heart Rhythm O2)
Background: Fragmented QRS complex (f-QRS) on a 12-lead electrocardiogram (ECG) has been associated with myocardial scars. However, its diagnostic accuracy for detecting myocardial scars assessed by cardiac magnetic resonance (CMR) imaging remains uncertain. Objective: To evaluate the diagnostic performance of f-QRS for detecting myocardial scars assessed by 3.0 CMR. Methods: Patients who underwent 3.0 Tesla CMR between May 2020 and May 2023 were included. A 12-lead ECG was assessed for f-QRS, defined as the presence of an R' wave or notching in the nadir of the S wave in at least 2 contiguous leads. The diagnostic performance of f-QRS in detecting myocardial scars in corresponding left ventricular segments was analyzed. Results: Overall, 1692 patients were included. f-QRS presented in 826 (49%) participants which were more prevalent in men (59.4% vs 46.0%), those with a history of coronary artery disease (26.4% vs 20.6%), and those with myocardial scars (48.9% vs 37.3). The sensitivity and specificity of f-QRS from ECG were 25.6% and 88.7% for anterior; 22.1% and 91.5%, for lateral; and 42.9% and 63.4% for inferior segments. Conclusion: f-QRS demonstrates high specificity for detecting myocardial scars on CMR, though its sensitivity is limited.